The role of microbial associations in the development of implant-associated infection after primary total knee replacement - Babushkina I.V.; Bondarenko A.S.; Mamonova I.A.; Shpinyak S.P.; Ulyanov V.Yu. (Саратовский научно-медицинский журнал, 2018)
Aim: to study the role of microbial associations in the etiology of implant-associated infection, the peculiarities of associates antibiotic resistance, to propose informative methods for the microbiological diagnostics of mixed infections. Material and Methods. The biological samples from 488 patients with infectious complications after total knee replacement were studied. Microorganisms were isolated and identified using a BD BBL™ Crystal™ AutoReader analyzer and Crystal™ Enteric/ Nonfermenter ID Kit, Crystal™Gram-Positive ID Kit panels. Results. Polyetiological infectious complications comprise up to 21.4-24.8% out of the total number of implant-associated infection cases; microbial associations have broad microbial spectrum and various component structure. Specific gravity of clinically significant microorganisms — methicillin-resistant Staphylococcus aureus, polyresistant enterobacteria and nonfermentative Gram- negative bacteria is statistically higher (p<0.05) among the associates (38.2, 25.2, 64.3 and 72.8% respectively) than in monocultures (18.2, 11.8, 47.5 and 58.3% respectively). Microbiological methods should be modified in order to verify polyetiological implant-associated infection. Conclusion. The organization of microbiological monitoring of polyetiologi-cal implant-associated infections with detailed study of microbial associations structure, the monitoring of associates antibiotic resistance is necessary to optimize the diagnostics and causal treatment of this pathology.